2020
DOI: 10.1051/epjconf/202022504013
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the neutron-gamma ray discrimination performance at low neutron energy of a solution-grown stilbene scintillator

Abstract: The results of experiments performed with a Ø25 x 25 mm solution-grown stilbene crystal in mono-energetic neutron fields in the 80-to-230 keV energy range are presented. The goal of the measurements, performed at the AMANDE facility, was to explore the capabilities of this organic scintillator to measure neutrons at the lowest possible energy with good pulse shape discrimination (PSD). The time of flight (TOF) technique was used in order to help with the neutron-gamma discrimination. The data are collected via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…In 2019, additional tests were carried out at AMANDE with this stilbene detector coupled to a digital acquisition system (6) . These experiments showed that the set-up was capable of detecting neutrons down to less than 100 keV (7) using the ToF technique.…”
Section: Stilbene Scintillatormentioning
confidence: 99%
“…In 2019, additional tests were carried out at AMANDE with this stilbene detector coupled to a digital acquisition system (6) . These experiments showed that the set-up was capable of detecting neutrons down to less than 100 keV (7) using the ToF technique.…”
Section: Stilbene Scintillatormentioning
confidence: 99%